PURE STRUCTURALISM ANALYSIS OF THE MONOLOGUE MANUSCRIPT "AENG" PUTU WIJAYA - Tia Nurhayati; Anissa Nur Fatwa; Zita Fany Puteri Pratama; Wulan Safirah Permata; Adita Widara Putra (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
The objective of this analysis is to thoroughly dissect the intrinsic structure of the text, which includes themes, characters and characterization, plot, setting, point of view, language style, and messages. AENG features the character Alimin, a prisoner reflecting on his life journey as he faces imminent execution. Through dense and emotional narration, the script presents profound inner turmoil, social critique, and existential irony. The methodology employed is descriptive-qualitative, utilizing structural analysis based on pure structuralism literary theories. Data is gathered through literature review of the script, supplemented by scholarly studies from literary journals. The findings indicate that AENG embodies complex humanitarian values and a robust dramatic structure, making this monologue a reflection of the moral crisis in modern society. By addressing social realities through a structural approach, AENG offers a narrative that not only resonates with the reader's inner self but also stimulates collective awareness of justice and humanitarian values.